Data mining and decision-making (An Applied Study on Khashm Algirba Dam) - د. سيف الدين عثمان فتوح; د. الشفيع جعفر محمود (White Nile Journal for Studies and Research, 2014)
The use of techniques Data mining provides for institutions in all areas the ability to explore and focus on the most important information in the databases, also focusing techniques data mining as well as to build a future forecasts and exploration behavior and trends, which allows to take the right decisions and taken in a timely manner.